Consumer Perception of Dry‐Cured Ham – A Cross‐Cultural Study in Italy, Norway and Spain. Issue 6 (28th October 2013) - Hersleth, Margrethe; Næs, Tormod; Guerrero, Luis; Claret, Anna; Recchia, Annamaria; Dinnella, Caterina; Monteleone, Erminio
Abstract The main aim of this study was to explore Italian, Norwegian and Spanish consumers' sensory perception of dry‐cured ham. Six samples of dry‐cured ham, two Italian, two Norwegian and two Spanish, were profiled by trained panels in the three countries. Consumer samples of 30 respondents in each country elicited sensory descriptors for the six hams and subsequently rated the intensity of individual descriptors. Perceptual consensus product maps were derived from the Generalized Procrustes Analysis. Results revealed that all the four sensory modalities are important for the perception of dry‐cured ham and demonstrated a relatively large variation in vocabulary used for sensory description of hams in the three countries. Because of less familiarity with dry‐cured ham and a different eating culture, Norwegian consumers have a relatively limited vocabulary and do not agree well on the concepts for given descriptors. Attributes that were most frequently used across panels and countries were: red color, marbling, ripe/cured flavor and odor, saltiness, sweetness, firmness and tenderness. Practical Applications Food preferences and description of sensory properties in foods vary across cultures. Considering the global character of today's food market, it is crucial for the food industry to use proper and meaningful words to communicate their products. Moreover, communication of sensory product attributes to consumers creates both sensory‐based and hedonic‐based expectations to the sensory quality. It is essential that these expectations are met during consumers eating experience. Finding in this study demonstrate a relatively large variation in vocabulary used for description of dry‐cured ham in Norway, Italy and Spain. This is mainly due to differences in familiarity with the product and different cultural eating experiences. Accordingly, it is important to tailor the communication of products according to the relevant consumer segment.